A nutritional approach to managing exercise-induced asthma - Mickleborough, T. D. (Exercise and Sport Sciences Reviews, 2008)
Exercise-induced asthma (EIA) is traditionally treated with the use of pharmacotherapy. However, there is now convincing evidence that a variety of dietary factors such as elevated omega-3 polyunsaturated fatty acids and antioxidant intake, and a sodium-restricted diet can reduce this condition. New therapies that are safe, effective, and likely to be used by individuals with EIA are needed.